Personality / An Integrative Approach - Mayer Stephan F; Sutton Karen (Prentice Hall, 1996)
Theoretical and Methodological Foundations, General Overview and Methodological Foundations, Theoretical Foundations, The Psychodynamic Tradition, The Trait and Humanistic Traditions, The Learning and Cognitive and Cognitive-Learning Traditions, An Organizational Framework, The Person and the Situation and Their Interaction, Empirical Expositions, The Biological Basis of Personality, Emotionality, Introversion and Extraversion and Impulsivity, Intelligence, The Self, The Cognitive Self, The Private and Public Self, Locus of Control and Self-Efficacy, Acquired Needs, Achievement Motivation, The Need for Power, Topics and Issues, Sex-Typing and Androgyny, Personality and Health.